Pengaruh Price To Book Value (PBV) Dan Likuiditas Saham Terhadap Stock Split Dan Dampaknya Terhadap Kinerja Pasar - Riky Setiawan; Yeterina Widi Nugrahanti (Universitas Kristen Wira Wacana Sumba, 2012)
The purpose of this study is to investigate whether PBV and stock’s liquidity have influence toward firms to perform stock split and the effect of stock split towards market’s value. Stock’s liquidity is measured by Trading Volume Activity while market’s value is measured by Toin’s Q. This research uses financial performance (Earnings per Share) as a control variable. The methods used is purposive in which in this study obtained 31 splitting firms and 31 non splitting firms during period 2005-2009. The analysis tools used in this study are logistic regression and paired t-test. The result shows that trading volume has negative influence toward firms to perform stock split. Also, the result shows that there are differences in market’s value after and before they perform stock split based on Tobin’s q.Keywords : Stock Split, Price to Book Value, Trading Volume, Earning per Share and Tobin’s q.